Management of herpes labialis triggered by emotional stress - Herlambang Prehananto; Kus Harijanti (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2016)
Background: Herpes labialis is a form of secondary or recurrence of primary herpes simplex infection. Herpes simplex virus is latent. It can reactivate due to reactivation of the virus induced by emotional stress, high fever, ultraviolet exposed, oral mucosal or nerve tissue trauma, immunosuppression condition, and hormonal disorders. Purpose: The study aimed to report the management of patients with herpes labialis on the lower lip triggered by emotional stress. Case: A 58 year-old woman complained of pain in her lower lip. The patient had suffered from the pain since one month ago. The patient had been treated with a lip ointment, triamcinolone acetonid 0.1% (Kenalog®), for 2 weeks, but became thick, dry, and worse. She said that she got many calamities related to her family, leading to the increased busyness and psychologically distressed conditions. Extra oral examination of the lower lip showed erythematous erosion sized 4x4 mm, yellowish red crusting sized 3x4 mm, and translucent multiple vesicles sized 1x1 mm with well circumscribed as well as irregular edges. On palpation submandibular lymph nodes, dextra and sinistra were palpable, rubbery, mobile and painless. Based on intra-oral examination, however, there were no abnormalities. Case management: The diagnosis was determined based on anamnesis, clinical examinations, and supporting examination of Ig M and anti HSV-1 Ig G. The patient then was prescribed systemic and topical Acyclovir. Conclusion: Some laboratory tests are necessary to confirm the diagnosis and determine the accurate therapy of herpes labialis in addition to the history and clinical features.